A Solvent‐Exposed Cysteine Forms a Peculiar NiII‐Binding Site in the Metallochaperone CooT from Rhodospirillum rubrum. Issue 67 (6th November 2019) - Alfano, Marila; Veronesi, Giulia; Musiani, Francesco; Zambelli, Barbara; Signor, Luca; Proux, Olivier; Rovezzi, Mauro; Ciurli, Stefano; Cavazza, Christine
Abstract: In Rhodospirillum rubrum, the maturation of carbon monoxide dehydrogenase (CODH) requires three nickel chaperones, namely Rr CooC, Rr CooT and Rr CooJ. Recently, the biophysical characterisation of the R r CooT homodimer and the X‐ray structure of its apo form revealed the existence of a solvent‐exposed Ni II ‐binding site at the dimer interface, involving the strictly conserved Cys2. Here, a multifaceted approach that used NMR and X‐ray absorption spectroscopies, complemented with structural bio‐modelling methodologies, was used to characterise the binding mode of Ni II in Rr CooT. This study suggests that Ni II adopts a square‐planar geometry through a N2 S2 coordinating environment that comprises the two thiolate and amidate groups of both Cys2 residues at the dimer interface. The existence of a diamagnetic mononuclear Ni II centre with bis‐amidate/bis‐thiolate ligands, coordinated by a single‐cysteine motif, is unprecedented in biology and raises the question of its role in the activation of CODH at the molecular level. Abstract : Absolutely extraordinary : A multifaceted approach involving spectroscopic methods and structural bio‐modelling methodologies was used to characterise the binding mode of Ni II in the nickel chaperone Rr CooT, which is essential to the maturation of carbon monoxide dehydrogenase (CODH) in Rhodospirillum rubrum .